Educational programs to improve nurses' knowledge, attitude, and practice in adolescent and young adult health: An integrative review. (November 2022) - Ramjan, Lucie M.; Maneze, Della; Krstevska, Elena; Pathrose, Sheeja Perumbil; Lewis, Peter
Abstract: Objective: Nurses working in adolescent health often lack educational opportunities to develop their knowledge and practical skills to address the challenges faced by adolescents and young adults. This integrative review synthesised the evidence from peer-reviewed research that focused on educational programs to improve nurses' knowledge, attitude, and practice in adolescent and young adult health. Design: The five-stage framework by Whittemore and Knafl guided the integrative literature review and was reported according to the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) statement. Data sources: A single search strategy was replicated across five electronic databases (CINAHL Plus, APA PsycInfo, PubMed, Scopus, and ERIC). Studies of educational interventions or training programs for nurses on adolescent and young adult health, published in English in the last 10 years were included. Review methods: All studies found were reviewed for relevance independently by two authors, who likewise critically appraised the quality using the "Critical appraisal checklist for an article on an educational intervention" adapted from Morrison et al. (1999), with a third author providing consensus. Data were extracted using study specific standardised proforma and thematically analysed. Results: Seven studies met the inclusion criteria. Topics covered included cancer care, mental health and self-harm, with only one program including general adolescent health. A mix of face-to-face and digital asynchronous mode of delivery was employed in these programs with multi-strategic approaches used to enhance accessibility and engagement. While all studies reported improvement in knowledge and practice, including enhanced communication skills, some studies reported limited change in attitude. Success of the interventions was attributed to the flexibility of programs to accommodate nurses' workloads. Conclusion: Education interventions for nurses delivering care to adolescent and young adults enhance knowledge and skills, however, programs with institutional support for flexibility and accessibility are needed to influence a positive change in attitude.